Strategi Meningkatkan Layanan Masyarakat dan Penawaran Produk pada PT Pegadaian (Persero) UPC Kapasan Surabaya - Maslahatul Ummah; Pregnandia Ladina (Fakultas Teknik Universitas Cenderawasih, 2024)
I nternship is an essential part of the educational process that provides students with the opportunity to gain practical experience in the workplace. This study aims to evaluate the experience gained during the internship at PT. Pegadaian (Persero) UCP Kapasan, which took place from July 8 to November 8, 2024. During the internship period, participants gained insight into the management of Pegadaian’s products, organizational skills, teamwork, as well as communication and customer service. Additionally, the interns gained experience in marketing products and processing customer data. This internship experience helped participants develop interpersonal skills, accuracy, and work discipline. The results of this internship activity provide valuable insights for improving internship programs in the future.